(untitled) (Società e diritti, 2022)
The contribution refers to the roots of Russian-Ukrainian conflict originating from the aggression of Moscow in Kiev on February 24, 2022 to analyze, on the one hand, the Russian autocratic involution over the two decades led by Putin, and on the other hand, the genesis of the Russian invasion of Ukraine from the historical-institutional perspective. Furthermore, the repercussions on the conflict of the uncertain evolution of the Ukrainian system of government are examined as well as the international effects of the same conflict where the battleground of the Donbass appears to constitute a piece of Moscow’s strategy based on the reelaboration of the concept of “soviet people”.